Pasteurella organism: Its isolation and identification from pneumonic lungs of goats in Ethiopia (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The objective of this study was to isolate and identify Pasteurella spp. associated with pneumonic lungs showing respiratory signs of goats in Ethiopia.Materials and methods: A total of 2400 goats that were slaughtered at the Hashims Ethiopian Livestock and Meat Export abattoir, Ethiopia were randomly selected for this cross-sectional study during the period of October 2013 to July 2014. Detail ante-mortem, and post-mortem (PM) lesions were inspected, and the suspected samples were collected aseptically from the lungs. Among 2400 goats, 31(1.29%) goats were not slaughtered because these goats showed severe clinical signs. Thus, 2369 goats were slaughtered finally. The collected samples were subjected for isolation and identification of bacterial species following conventional methods such as culture and biochemical examinations.Results: Out of 2400 goats examined, 960(40%) animals showed different abnormal respiratory signs. Based on PM findings, 16.21% (n=384/2369) lungs were found as pneumonic, of which 78.38% (n=301/384) were found to be associated with Pasteurella organism. The overall prevalence of Pasteurella organism (Mannheimia haemolytica and Pasteurella multocida) was 12.71% (n=301/2369). In this study, youngers and goats with medium body condition score (BCS) had greater probability (P